Replacement of Cobalt in Lithium-Rich Layered Oxides by n-Doping: A DFT Study - Mariarosaria Tuccillo (MDPI AG, 2021)
The replacement of cobalt in the lattice of lithium-rich layered oxides (LRLO) is mandatory to improve their environmental benignity and reduce costs. In this study, we analyze the impact of the cobalt removal from the trigonal LRLO lattice on the structural, thermodynamic, and electronic properties of this material through density functional theory calculations. To mimic disorder in the transition metal layers, we exploited the special quasi-random structure approach on selected supercells. The cobalt removal was modeled by the simultaneous substitution with Mn/Ni, thus leading to a p-doping in the lattice. Our results show that cobalt removal induces (a) larger cell volumes, originating from expanded distances among stacked planes; (b) a parallel increase of the layer buckling; (c) an increase of the electronic disorder and of the concentration of Jahn–Teller defects; and (d) an increase of the thermodynamic stability of the phase. Overall p-doping appears as a balanced strategy to remove cobalt from LRLO without massively deteriorating the structural integrity and the electronic properties of LRLO.